2002
DOI: 10.1073/pnas.092538699
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling paleodistribution models and comparative phylogeography in the Wet Tropics rainforest land snailGnarosophia bellendenkerensis(Brazier 1875)

Abstract: Comparative phylogeography has proved useful for investigating biological responses to past climate change and is strongest when combined with extrinsic hypotheses derived from the fossil record or geology. However, the rarity of species with sufficient, spatially explicit fossil evidence restricts the application of this method. Here, we develop an alternative approach in which spatial models of predicted species distributions under serial paleoclimates are compared with a molecular phylogeography, in this ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
395
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(413 citation statements)
references
References 44 publications
14
395
2
2
Order By: Relevance
“…Concordance between phylogeographic patterns was also observed in other regions, such as central America, in several rodent species (ie Bermingham and Martin, 1998;Riddle et al, 2000;Sullivan et al, 2000), southern America in various bat, rodent and marsupial species (ie da Patton, 1993, 1998;Ditchfield, 2000) as well as in Australian birds, reptiles (Joseph et al, 1995) and snails (Hugall et al, 2002). Furthermore, Lessa et al (2003) detected a strong concordance of demographic expansion in North American mammals after the last ice age, 10 000 years ago.…”
Section: Introductionmentioning
confidence: 73%
“…Concordance between phylogeographic patterns was also observed in other regions, such as central America, in several rodent species (ie Bermingham and Martin, 1998;Riddle et al, 2000;Sullivan et al, 2000), southern America in various bat, rodent and marsupial species (ie da Patton, 1993, 1998;Ditchfield, 2000) as well as in Australian birds, reptiles (Joseph et al, 1995) and snails (Hugall et al, 2002). Furthermore, Lessa et al (2003) detected a strong concordance of demographic expansion in North American mammals after the last ice age, 10 000 years ago.…”
Section: Introductionmentioning
confidence: 73%
“…Many of these studies have focussed on organisms with a high-dispersal ability (basically vertebrates, Cabanne et al, 2008;D'Horta et al, 2011) that may hinder making fine-scale predictions. Specialized and low-dispersal organisms can preserve the genetic signature of the past climate and geological events in small geographical areas (Hugall et al, 2002;Sunnucks et al, 2006;Marske et al, 2011). Thus, using a low-dispersal organism maximizes the probability, given comparable sampling designs, of detecting a finerscale genetic structure within the AF relative to other studies using higher-dispersal co-distributed organisms.…”
Section: Introductionmentioning
confidence: 93%
“…They concluded that the more habitat-specialised a species is to rainforests, the earlier it would have been isolated into separate subpopulations by the Pleistocene's increasingly severe cycles of aridity. They also detected a phylogeographic break in rainforest species north of Cairns across what is known as the Black Mountain Barrier (see Hugall et al 2002).…”
Section: Explosion Of Phylogeography: the Mid-to Late 1990smentioning
confidence: 99%